2018
DOI: 10.1002/jso.25126
|View full text |Cite
|
Sign up to set email alerts
|

The importance of indocyanine green near‐infrared fluorescence angiography in perfusion assessment in vascularized omentum lymphatic transplant

Abstract: Normal flap perfusion is a requisite for successful VOLT harvest. However, over half the patients had some degree of abnormal perfusion irrespective of prior abdominal surgery. Indocyanine green angiography is an important tool in ensuring a healthy lymphatic reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Furthermore, ischemic areas of native omentum may be present upon transfer, decreasing the amount of flap available to be split. Coriddi et al demonstrated 53.9% of patients had significant portions of ischemic omentum requiring removal of portions of the flap, regardless of history of abdominal surgery (Coriddi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, ischemic areas of native omentum may be present upon transfer, decreasing the amount of flap available to be split. Coriddi et al demonstrated 53.9% of patients had significant portions of ischemic omentum requiring removal of portions of the flap, regardless of history of abdominal surgery (Coriddi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional drainage pattern of the in situ omentum requires dual venous anastomosis to restore a physiologic state. Several authors have cited venous hypertension, and subsequent congestion leading to flap loss in omental flaps (Coriddi et al, ; Kenworthy et al, ; Nguyen et al, ). If the flap were to be split, a total of four venous anastomosis would have to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 More recently, vascularized omentum lymphatic transplant and mesenteric node transfer have eliminated the risk of donor site lymphedema. 44,45 The omentum also provides a large surface area that may be beneficial in certain cases and can be split into 2 flaps, one placed proximally and one distally (Fig. 5).…”
Section: Frontiers In Lymphatic Reconstructionmentioning
confidence: 99%